Development of chitosan-based edible biocomposite films incorporated with Kumquat peels extract as food packaging - Sahin, Fatmagul; Kucuk, Ilknur; Doymaz, Ibrahim (SCIENTIFIC PUBL-INDIA, 2019)
Edible films incorporate with various ratio of Kumquat peel extract were prepared by using solvent casting techniques. In order to determine the effect of Kumquat peel concentration, the biofilms have been characterized by physical properties such as moisture content, swelling degree, water solubility, water vapor permeability, color and transparency as their structures were confirmed by Scanning Electron Microscope (SEM). In addition, the mechanical properties have been determined with the tensile strength and elongation in terms of breakage of the prepared films. It has been observed that the amount of moisture, swelling, and solubility of the films changed between 30.95-22.05%, 177.96-24.8% and 34.58-54.47%, respectively. It has been observed that the amount of moisture and the degree of swelling of the films decreased and the solubility values increased with the increase of Kumquat peel extract. The water vapor permeability, thickness and density range values of the films have been as follows: 1.039 g H2O Pa-1 s(-1) m(-1) and 0.989 g H2O Pa-1 s(-1) m(-1), 0.0670 to 0.0554 mm, 0.86 g/cm(3) to 0.79 g/cm(3). It has been determined that the ratio of Kumquat bark extract does not cause a significant change on the water vapor permeability, thickness and density values of the films. With the increasing of the concentration of the Kumquat peel extract in the film structure and the films exhibit a more flexible property and the tensile strength at 33.28-13.5 MPa has been observed to vary between 7.74% and 20.57%. Results indicate that the chitosan-based films incorporated with Kumquat peel extract can be an alternative for food packaging.
Keywords: Chitosan; Kumquat; edible film; biopolymer; food packaging; PHYSICAL-PROPERTIES; NANOCELLULOSE; OPTIMIZATION; GLYCEROL; Chemistry